The shadow: alter-visibility in an empire of the seen. Issue 1 (2nd January 2016) - Welsh, John
Abstract : The article interrogates the concept of Multitude in capitalist society and challenges the simple notion of social exclusion as an operative force in contemporary social formations and their spatial dispositions. The Shadow will be offered as a spatial and psychosocial relational horizon of differentiation systemically inscribed into the social architecture, operating under a legitimating discourse of transparency politics. The concept succinctly characterizes the personal and social experiences of political opacity in twenty-first-century biopolitical capitalist society, and the exploitation of living labour by a topological apparatus of 'alter-visibility'. The piece explores the emergence of various 'Shadowlands' in the social materiality generated by spatial technologies of political and social control. By assuming the juxtaposing archetype of the Trickster, and a dialectical politics opened up by the Shadow's technology of alter-visibility, the article argues for the potential realization of the Multitude concept out of a personal ethical praxis and counter-conduct based on the Trickster concept against the consigning and coding power of capitalist Empire and the spatio-temporal shadowlands that it generates. The psychosocial dialectical potential in the figure of the Trickster derives from its enantiodromic confrontation with the Shadow in a critical heterotopic politics of disaster, juxtaposition, and 'schizophrenic' rebellion.